Gendered exposure, vulnerability, and response: Malaria risk in a changing climate in Western Kenya - Onyango, Esther; Maguire, Rowena (Frontiers in Climate, 2022)
Climate change has been linked to increasing rates of malaria infection in western Kenya. Projections show an increased risk of malaria infection under climate change scenarios, impacting vulnerable populations and placing millions of people at risk. Developing suitable risk management strategies requires understanding the hazard, exposure, vulnerability and response to climate change and malaria risk in the context of other local environmental, socio-economic and socio-cultural factors (including gender) that influence exposure, vulnerability and capacity to cope. This paper draws upon two analytical frameworks, using data gathered from focus group discussions with small-scale farmers in Western Kenya: The Intergovernmental Panel on Climate Change (IPCC) Risk Assessment Framework; and Feminist Political Ecology (FPE) to analyse social constructions underpinning farming responsibilities and decision-making power and how these influence the gendered dimensions of exposure, vulnerability and response to climate change and malaria risk in the community. This paper finds that gender influences the risk of malaria through feminization of agricultural activities in the region, socially constructed gendered responsibilities for care and farm work, which increases exposure and vulnerability to mosquito bites and malaria infection, and socially constructed rights of women to make farming decisions and manage farm income, which influences their capacity to manage risk and cope in the long term. Drawing on these findings, this paper proposes that an intersectional gender lens needs to be incorporated into climate and malaria adaptation policy and programming. It concludes with recommendations for implementing the UNFCCC Enhanced Lima Work Program on Gender at the country levels and the development of gender-responsive climate change and malaria risk management.